A Foldable Aqueous Zn‐Ion Battery with Gear‐Structured Composite as Freestanding Cathode. Issue 10 (4th January 2023) - Liu, Jinyun; Zhu, Yajun; Han, Tianli; Zhang, Huigang; Hu, Chaoquan; Niu, Junjie
Abstract: A foldable battery with high flexibility provides great potential in various wearable electronic devices for health and fitness tracking, chronic disease management, performance monitoring, navigation tracking, and portable gears for soldiers. We report a highly flexible, self‐healing Zn‐ion battery with a free‐standing cathode that is composed of a 3D gear‐like NH4 V4 O10 @C composite on carbon paper. The battery retained a capacity of up to 102.4 mAh g −1 even after being folded 60 times with a high angle of 180°. An aqueous hydrogel consisting polyvinyl alcohol, glycerin and Zn(CF3 SO3 )2 was used as electrolyte, which showed as high as 580 % tensile strain under a loading weight of 78 N. The battery exhibited a better capacity retention of over 100 mAh g −1 and Coulombic efficiency of over 99.8 % after cutting and twisting to 90°, thereby indicating a great self‐healing performance. The gear‐like geometry greatly improved the volume accommodation due to the increased interval space between the blades and the outward configuration. Meanwhile the Zn 2+ ionic conductivity was improved by rapid re‐binding of many existing hydroxy groups from the electrolyte and the enhanced contact surface area and diffusion route from the cathode material. The highly flexible, safe aqueous Zn‐ion battery opens a practical way to power various carry‐on electronics under mechanical agitation. Abstract : Gearing up for portable devices : A flexible, self‐healing Zn‐ion battery uses a freestanding cathode that is composed of a 3D gear‐like NH4 V4 O10 @C composite on carbon paper. The battery retained a capacity of over 102.4 mAh g −1 after being folded 60 times with a high angle of 180°, and a better capacity retention of >100 mAh g −1 after cutting and twisting to 90°. The highly flexible, safe, aqueous Zn‐ion battery opens up a practical way to power various carry‐on electronic devices.